In-vitro NMR Studies of Prostate Tumor Cell Metabolism by Means of Hyperpolarized [1-13C]Pyruvate Obtained Using the PHIP-SAH Method - Cavallari, Eleonora; Carrera, Carla; Di Matteo, Ginevra; Bondar, Oksana; Aime, Silvio; Reineri, Francesca (Frontiers in Oncology, 2020)
Nuclear Magnetic Resonance allows the non-invasive detection and quantitation of metabolites to be carried out in cells and tissues. This means that that metabolic changes can be revealed without the need for sample processing and the destruction of the biological matrix. The main limitation to the application of this method to biological studies is its intrinsic low sensitivity. The introduction of hyperpolarization techniques and, in particular, of dissolution-Dynamic Nuclear Polarization (d-DNP) and ParaHydrogen Induced Polarization (PHIP) is a significant breakthrough for the field as the MR signals of molecules and, most importantly, metabolites, can be increased by some orders of magnitude. Hyperpolarized pyruvate is the metabolite that has been most widely used for the investigation of metabolic alterations in cancer and other diseases. Although d-DNP is currently the gold-standard hyperpolarization method, its high costs and intrinsically slow hyperpolarization procedure are a hurdle to the application of this tool. However, PHIP is cost effective and fast and hyperpolarized pyruvate can be obtained using the so-called Side Arm Hydrogenation approach (PHIP-SAH). The potential toxicity of a solution of the hyperpolarized metabolite that is obtained in this way is presented herein. HP pyruvate has then been used for metabolic studies on different prostate cancer cells lines (DU145, PC3 and LnCap). The results obtained using the HP metabolite have been compared with those from conventional biochemical assays.